Correlation between serum ferritin level and severity of dengue fever in a tertiary care center: an observational study - Murmu, Akash R.; R., Mubarak (International Journal of Research in Medical Sciences, 2021)
Background: Serum ferritin is an acute phase protein and elevated levels of ferritin have been associated with the pathogenesis of many inflammatory infectious viral diseases. Dengue is a mosquito-borne tropical infection that caused by the dengue virus. TNFα and interleukin 1α, another proinflammatory cytokine, transcriptionally induce the H-chain of ferritin. Therefore, serum ferritin can be used as a prognostic marker for dengue severity. Methods: This is a case control study conducted between July 2017 to December 2018. Results: On the 3rd day of fever, the median values of serum ferritin in dengue, fever without warning signs, with warning signs, and severe dengue were 513.5 ng/ml, 1002 ng/ml and 2352.4 ng/ml respectively. On the 7th day of fever, the median values were 474 ng/ml, 900 ng/ml, and 2949 ng/ml respectively. Serum ferritin 1247 ng/ml on day 3 has a sensitivity of 96.4% and specificity of 91% for prediction of severity. Area under the curve for serum ferritin on day 3 was 0.963 (95% confidence limit: 0.934-0.991). Serum ferritin 1050 ng/ml on day 7 has a sensitivity of 98.2 % and specificity of 93% for prediction of severity. Area under the curve for serum ferritin on day 7 was 0.977 (95% confidence limit: 0.957-0.998). Conclusions: Elevation of serum ferritin was significantly seen in those with severe dengue. Serum ferritin can be used as a prognostic marker for dengue severity. Day 3 serum ferritin can be used as a prognostic marker for dengue severity.